Sero-surveillance of Canine Distemper in Dogs - Joshi, Vedanshee R.; Bhanderi, Bharat B.; Mathakiya, Rafiyuddin A.; Jhala, Mayurdhvaj K.; Desai, Dhruv N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was undertaken on serological survey of Canine distemper (CD) in dogs in various districts of Gujarat state. Serasamples from 86 CD suspected dogs were collected from Anand, Navsari, Ahmedabad and Vadodara districts for detection of antibodies against CDV. Out of 86 sera samples screened, 35 were found positive for CD by indirect ELISA, indicating overall seroprevalence to be 40.70%. Location wise, seroprevalence was found to be higher 61.53% (16/26) in Navsari district, followed by 30.43% (14/46) in Anand district. With low sample size, Vadodara and Ahmedabad districts showed 40.00% (2/5) and 33.33% (3/9) seroprevalence, respectively. Sex-wise seroprevalence of CD was found to be higher in females (47.36%) than in males (35.41%), whereas age-wise seroprevalence was found to be higher in 6 to 12 months of age group (43.03%) than >12–24 months of age group (14.28%)
Keywords: Canine distemper; Dogs; Gujarat; Serological Survey